2016
DOI: 10.1016/j.physbeh.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic modulation of hippocampal cell signaling and associated effects on learning and memory

Abstract: The hippocampus is a key brain structure involved in synaptic plasticity associated with long-term declarative memory formation. Importantly, nicotine and activation of nicotinic acetylcholine receptors (nAChRs) can alter hippocampal plasticity and these changes may occur through modulation of hippocampal kinases and transcription factors. Hippocampal kinases such as cAMP-dependent protein kinase (PKA), calcium/calmodulin-dependent protein kinases (CAMKs), extracellular signal-regulated kinases 1 and 2 (ERK1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 211 publications
(258 reference statements)
2
32
0
Order By: Relevance
“…In further support of nicotine modulating synaptic plasticity, nicotine can alter key cell signaling kinases and transcription factors known to modulate hippocampal learning and plasticity such as PKA, ERK1/2, and CREB (for review, see Kutlu and Gould 2016). For example, Gould et al (2014b) showed that infusions of a subthreshold dose of the PKA inhibitor PKI 14 -22 amide into the dorsal hippocampus reversed enhancement of contextual fear conditioning by acute nicotine.…”
Section: Modulation Of Hippocampal Plasticity By Nicotinementioning
confidence: 99%
See 1 more Smart Citation
“…In further support of nicotine modulating synaptic plasticity, nicotine can alter key cell signaling kinases and transcription factors known to modulate hippocampal learning and plasticity such as PKA, ERK1/2, and CREB (for review, see Kutlu and Gould 2016). For example, Gould et al (2014b) showed that infusions of a subthreshold dose of the PKA inhibitor PKI 14 -22 amide into the dorsal hippocampus reversed enhancement of contextual fear conditioning by acute nicotine.…”
Section: Modulation Of Hippocampal Plasticity By Nicotinementioning
confidence: 99%
“…Moreover, CREB phosphorylation in the hippocampus was also inhibited following chronic ethanol exposure while ethanol withdrawal enhanced hippocampal CREB (Bison and Crews 2003). The ethanol-induced changes in MAPK-CREB pathway are crucial to understanding the molecular mechanisms underlying the hippocampal deficits during chronic ethanol exposure because numerous studies have shown that activation of this cell signaling pathway is necessary for long-term memory formation (e.g., Atkins et al 1998;Vianna et al 2000) and LTP (e.g., Winder et al 1999;Kelleher et al 2004; for review, see Kutlu and Gould 2016). Overall, these studies show that chronic ethanol can inhibit cell signaling cascades involved in learning through activation of GABAergic receptors and blockage of NMDA receptors in the hippocampus.…”
Section: Effects Of Prolonged Alcohol Exposure On Hippocampal Functionmentioning
confidence: 99%
“…Therefore, nicotine-induced plasticity in regions that regulate memory consolidation and learning may also mediate nicotine-seeking behavior. Nicotine has been shown to both improve working memory and to enhance hippocampal-dependent learning [230]. In contrast, chronic nicotine administration, when delivered at high doses, enhances hippocampal neurogenesis, the growth of new neurons, specifically in the dentate gyrus region of the hippocampus [231-233].…”
Section: Neurophysiological Mechanisms Underlying Nicotine-seeking Bementioning
confidence: 99%
“…In the hippocampus, nAChRs are densely expressed on inhibitory interneurons [242], and nicotine-induced hippocampal LTP is at least in part dependent on local disinhibition of granule cells [243]. Nicotine-mediated hippocampal plasticity and its role in learning and plasticity have been discussed extensively [230, 244, 245]. …”
Section: Neurophysiological Mechanisms Underlying Nicotine-seeking Bementioning
confidence: 99%
“…Nicotinic acetylcholine receptors (nAChRs) regulate a variety of cell signaling cascades that are important for various behavioral processes such as long-term memory formation (see Kutlu & Gould, 2016 for a review). In the hippocampus, nAChRs gate calcium (Ca 2+ ) and sodium into the cell (Wonnacott, 1997).…”
Section: Introductionmentioning
confidence: 99%